Comprehensive Analysis of Football Player Market Valuation: Integrating Performance Metrics and Marketability Factors - Cai, Jiaxuan (Transactions on Economics, Business and Management Research, 2024)
In the fast-paced world of professional football, valuing players involves numerous factors. This paper explores the determinants of football players’ market values using a mixed-methods approach. Quantitative data from sources like Opta Sports, Transfermarkt, and the CIES Football Observatory, along with qualitative insights from semi-structured interviews with industry experts, were analyzed. The quantitative analysis found that goals scored and social media followers significantly predict player market value, with a strong social media presence amplifying the impact of goals. Non-linear relationships revealed diminishing returns on market value as social media followers increase. Qualitative insights highlighted the importance of media presence, cultural impact, and digital engagement in shaping player valuations. Players frequently featured in media, seen as cultural icons, or active on digital platforms tend to have higher market values. A comparison with historical data showed a growing emphasis on marketability and digital presence. The study concludes that integrating quantitative performance metrics with qualitative marketability factors is crucial for accurate player valuation. This holistic approach offers valuable insights for clubs, agents, and policymakers, enhancing decision-making in player transfers and contract negotiations. The research contributes to sports management and economics by providing a comprehensive framework for managing player assets in professional football.